2022
DOI: 10.3390/nano12060946
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of Ni(OH)2 Modified Two-Dimensional ZnIn2S4 Heterostructure for Boosting Hydrogen Evolution under Visible Light Illumination

Abstract: Developing efficient catalysts to produce clean fuel by using solar energy has long been the goal to mitigate the issue of traditional fossil fuel scarcity. In this work, we design a heterostructure photocatalyst by employing two green components, Ni(OH)2 and ZnIn2S4, for efficient photocatalytic H2 evolution under the illumination of visible light. After optimization, the obtained photocatalyst exhibits an H2 evolution rate at 0.52 mL h−1 (5 mg) (i.e., 4640 μmol h−1 g−1) under visible light illumination. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…3d shows the average exciton PL lifetime (t avg ), which was measured using eqn (2): It is found that the extracted PL lifetime of the ultrathin 2D Ag 2 SO 4 nanosheets is B2.06 ns (Table S1, ESI †), which offers high-performance optoelectronic chemical sensing due to their long exciton lifetime compared with other 2D materials such as PdSO 4 , GaSe, and ZnIn 2 S 4 . 20,68,69 Given such a prolonged excitonic lifetime, the photoinduced electron-hole pairs can be further separated from the 2D material body, forming trions to participate in the absorptive behavior of gas molecules with the increasing charge density on the material surface. The dispersion of obtained 2D Ag 2 SO 4 nanosheets was dropcast onto resistive transducer substrates to fabricate gas sensors.…”
Section: Resultsmentioning
confidence: 99%
“…3d shows the average exciton PL lifetime (t avg ), which was measured using eqn (2): It is found that the extracted PL lifetime of the ultrathin 2D Ag 2 SO 4 nanosheets is B2.06 ns (Table S1, ESI †), which offers high-performance optoelectronic chemical sensing due to their long exciton lifetime compared with other 2D materials such as PdSO 4 , GaSe, and ZnIn 2 S 4 . 20,68,69 Given such a prolonged excitonic lifetime, the photoinduced electron-hole pairs can be further separated from the 2D material body, forming trions to participate in the absorptive behavior of gas molecules with the increasing charge density on the material surface. The dispersion of obtained 2D Ag 2 SO 4 nanosheets was dropcast onto resistive transducer substrates to fabricate gas sensors.…”
Section: Resultsmentioning
confidence: 99%
“…54 The absorption spectrum of pure Ni(OH) 2 consisted of two wide absorption bands at 390-500 nm and 600-800 nm, corresponding to the d-d transition of Ni. 55,56 Compared with pure ZIS, the light absorption of the Ni-ZIS composites in the range of 300-500 nm had decreased due to the light shielding effect, while their visible-light absorption (500-800 nm) increased slightly. This result further confirms the deposition of Ni(OH) 2 on the surface of ZIS.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2a exhibits the survey spectra of the materials under study, which indicate the absence of any contaminating impurities in both graphene derivatives. This fact is reflected by the presence of exclusively C 1s, N 1s, and O 1s core-level signals centered at binding energies (BE) of 284.7 eV, 400.1 eV, and 532.5 eV, respectively, for the AmG, which are accompanied by a set of Zn-related lines, including a Zn 2p doublet at BEs of 1045.3 eV and 1022.1 eV, along with Zn LMM, Zn 3s, Zn 3p, and Zn 3d lines centered at 212.4 eV, 143.8 eV, 91.8 eV, and 13.2 eV, respectively [43,44]. Given the collected survey spectra, the elemental composition of the AmG and Am-ZnO samples was evaluated.…”
Section: Core-level Studies Of the Amg And Am-znomentioning
confidence: 99%